Riverbank filtration: an efficient and economical water treatment technology (2012)
Riverbank Filtration (RBF) is a water treatment technology that consists of extracting water from rivers by pumping wells located in the adjacent alluvial aquifer. During the underground passage, a series of physical, chemical, and biological processes take place, improving the quality of the surface water, substituting or reducing conventional drinking water treatment. Despite its extensive use in Europe and its emerging use in the United States, there are no scientific publications related to RBF use in Colombia, although apparently propitious settings exist. The main objective of this paper is to present a brief overview of the theoretical foundations of the technique, its benefits and limitations.